2012
DOI: 10.1007/s11033-012-1911-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, expression and characterization of a novel vacuolar protein sorting 4 gene in silkworm, Bombyx mori

Abstract: The vacuolar protein sorting 4 (Vps4) protein is essential for the multivesicular body (MVB) pathway, virus budding process and cytokinesis. Vps4 has been identified and characterized from many species, but not from silkworm Bombyx mori. In this study, we firstly identified and cloned the silkworm homologous gene for VPS4, expressed it in Escherichia coli, purified and characterized the protein designated as BmVps4. The BmVps4 cDNA contains an open reading frame of 1,314 bp, and encodes a protein of 438 amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In addition, mammalian Dlg can rescue the phenotype of a Drosophila Dlg mutant [11]. After the complete genome of B. mori was sequenced [12], the gene expression and regulation was widely analyzed [13,14,15]. However, there are no reports about the genes encoding the Scribble protein complex; including Scribble ( Scrib ), Discs large ( Dlg ) and Lethal giant larvae ( Lgl ) are found in silkworm, B. mori .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mammalian Dlg can rescue the phenotype of a Drosophila Dlg mutant [11]. After the complete genome of B. mori was sequenced [12], the gene expression and regulation was widely analyzed [13,14,15]. However, there are no reports about the genes encoding the Scribble protein complex; including Scribble ( Scrib ), Discs large ( Dlg ) and Lethal giant larvae ( Lgl ) are found in silkworm, B. mori .…”
Section: Introductionmentioning
confidence: 99%
“…The silkworm ( Bombyx mori ) is of economic value and also a research model for lepidopteran insects. To explore the silkworm MVB pathway, we previously identified BmVps4 and BmVta1 as silkworm homologues for Vps4 and Vta1, respectively (Xia et al , , ). In the present study, we globally characterized the transcription and protein expression profiles of BmVps4 and BmVta1 using fluorescence quantitative real‐time PCR (qRT‐PCR) and Western blots.…”
Section: Introductionmentioning
confidence: 99%
“…Silkworm ( Bombyx mori ) is an economic insect and a research model for Lepidoptera insects, and has also been used as a bioreactor to produce valuable bio-molecules. We previously identified a silkworm homologue for Vps4, named as BmVps4 ( Xia et al 2012 ). To expand our study of silkworm MVB pathway, in this report, we identified and cloned the silkworm homologous gene for VTA1 , expressed and characterized the protein designated as BmVta1.…”
mentioning
confidence: 99%